Histopathological changes in parotid gland following submandibular gland failure: an experimental animal study - Yildirim, Yavuz Sultan Selim; Kaygusuz, Irfan; Ozercan, Ibrahim Hanifi; Cetiner, Hasan; Sakallioglu, Oner; Akyigit, Abdulvahap; Duzer, Sertac (Assoc Brasileira Otorrinolaringologia & Cirurgia Cervicofacial, 2019)
Introduction: Submandibular glands are exposed to many effects due to diseases and therapeutic interventions. A study evaluating the effect of submandibular gland dysfunction on the parotid gland has not been presented in the literature. Objective: The aim of this study was to evaluate the histopathological changes in the parotid gland following submandibular gland failure. Methods: Three groups of seven randomly selected female New Zealand rabbits weighing 2500-3000g were studied. Unilateral and bilateral submandibular glands were removed in Groups 1 and 2, respectively. No procedure was performed in Group III, the control group. The parotid glands were removed 30 days later. Histological parameters were evaluated and graded between 0 (none) and 3 (severe). Differences between groups were compared using the Mann-Whitney U test. Results: Mean mucus accumulation in acinar cells was 2.57 +/- 0.53 and 1.71 +/- 0.75 in Groups 1 and 2, respectively (p < 0.05). This value was 0.57 +/- 0.53 in Group 3, which was significantly lower than in Groups 1 and 2 (p < 0.05). Mean dilatation of the intercalated ducts' lumen was 1.28 +/- 0.48 and 1.57 +/- 0.53 in Groups 1 and 2, respectively (p > 0.05). This value was 0.28 +/- 0.48 in Group 3, which was significantly lower than in Groups 1 and 2 (p < 0.05). Mean mucus accumulation in the intercalated ducts' lumen was 2.00 +/- 0.81 and 1.00 +/- 0.57 in Groups 2 and 3, respectively (p < 0.05). Conclusion: The findings of this study indicate that only 1 month after submandibular gland failure, the parotid glands exhibit significant changes. (C) 2018 Associacao Brasileira de Otorrinolaringologia e Cirurgia Cervico-Facial. Published by Elsevier Editora Ltda.
Alterações histopatológicas na glândula parótida após insuficiência da glândula submandibular: estudo experimental em animais
Keywords: Submandibular; Parotid; Submandibular gland failure; Histopathology